Cyber Operations and Collective Countermeasures under International Law. (11th February 2020) - Haataja, Samuli
Abstract: This article examines international law on the use of countermeasures against peacetime cyber operations that fall below the armed attack threshold. It focuses on collective countermeasures— ie, measures taken by states which have not been affected by the cyber operation but which have been requested to assist by the state victim to these operations. While a general right for non-injured states to take countermeasures has not been recognised in international law, this article demonstrates that there is some support for this right in circumstances where the injured state requests assistance from a non-injured state. It argues that a limited right of collective countermeasures should be recognised in the cyber context. This is warranted as it expands the remedies available to states subject to cyber operations and offers a way for less technologically advanced states to obtain assistance when subject to malicious cyber operations from their adversaries